Contribution to study of the concept, white collar or white collar crime (2022)
This article establishes as a general objective make a contribution to the study of the concept: "white collar crime", highlighting the incorporation of a new terminology, which generates theoretical contributions to the theory of unconventional crime. It is a basic research, which has a qualitative methodology, based on the study of cases, on white collar criminals, with a holistic and transdisciplinary vision, which adapts to the current world environment, supported by some disciplines of knowledge that are articulated to criminology, as a branch of law to enrich their knowledge.